If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4f + 5 = f + 9f + 5 Reorder the terms: 5 + -4f = f + 9f + 5 Reorder the terms: 5 + -4f = 5 + f + 9f Combine like terms: f + 9f = 10f 5 + -4f = 5 + 10f Add '-5' to each side of the equation. 5 + -5 + -4f = 5 + -5 + 10f Combine like terms: 5 + -5 = 0 0 + -4f = 5 + -5 + 10f -4f = 5 + -5 + 10f Combine like terms: 5 + -5 = 0 -4f = 0 + 10f -4f = 10f Solving -4f = 10f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-10f' to each side of the equation. -4f + -10f = 10f + -10f Combine like terms: -4f + -10f = -14f -14f = 10f + -10f Combine like terms: 10f + -10f = 0 -14f = 0 Divide each side by '-14'. f = 0 Simplifying f = 0
| x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x | | 4(2x+9)=-46+10 | | 2(x-3)-5(x-1)=4 | | -2x-5y=12forY | | b-10=10+10+9b | | 3(5x+6)-2(3-4x)=-11 | | 5z+14=7z-30 | | 4n^2-12n-320=0 | | x*x-100=0 | | 10-d=d-8 | | 340=x*490 | | 5(3t-4)-6=12t+4 | | -3r+6=r-6 |